High-performance composite aluminum film packaging bag and preparation method thereof

By adopting a three-layer structure, high-performance composite aluminum film packaging bag, and using two-component polyurethane adhesive to connect each layer, the problem of existing packaging bags being easily leaked after high-temperature cooking is solved, achieving better cooking resistance and heat storage effect.

CN119872048AActive Publication Date: 2025-04-25HUNAN GREAT WALL MINGTAI NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510173036.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-25
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

Existing composite aluminum film packaging bags are prone to composite layered leakage or broken bags after high temperature steaming, resulting in deterioration of packaged food.

Method used

High-performance composite aluminum film packaging bags with three-layer structure, including aluminum-plated film, intermediate film and heat-sealed film, are connected to each layer through a two-component polyurethane adhesive to optimize the composition of the adhesive to improve adhesion.

Benefits of technology

It significantly improves the steaming and cooking resistance of the packaging bag, prevents layered leakage at high temperatures, maintains the integrity of the packaging and the quality of the food, and also has heat storage performance, optimizing the consumer experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005274599860000121
    Figure BDA0005274599860000121
Patent Text Reader

Abstract

The invention discloses a high-performance composite aluminum film packaging bag and a preparation method thereof, and belongs to the technical field of packaging bags, the packaging bag is of a three-layer structure, the packaging bag sequentially comprises an aluminized film layer, a middle film layer and a heat-sealing film layer from outside to inside, the aluminized film layer, the middle film layer and the heat-sealing film layer are connected through a two-component polyurethane adhesive, and the two-component polyurethane adhesive is arranged between the middle film layer and the heat-sealing film layer. The two-component polyurethane adhesive comprises a main agent and a curing agent, the main agent contains a Ti 3A < l > C2 / S O2 composite material of distearoyl phosphatidyl ethanolamine-polyethylene glycol-silane modified menthol-loaded, and by optimizing the composition of the adhesive, not only is the tight connection among all layers realized, but also the cohesiveness of the adhesive under high-temperature and high-humidity conditions is greatly improved, and the adhesive can be applied to the field of adhesive materials. In addition, the packaging bag has certain heat storage performance, the stability of the internal temperature can be better kept, and the use experience of consumers is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging bags, and in particular relates to a high-performance composite aluminum film packaging bag and a preparation method thereof. Background Art

[0002] Plastic composite film is the most widely used food packaging material at present, especially the aluminum-plastic composite film formed by combining plastic and aluminum-plated film, which has good flexibility, moisture resistance, oxygen barrier, light shielding, shielding, antistatic, vacuum, color printing and other advantages, and is widely used in the fields of food, medicine, pesticides, chemicals, and electromechanical products. According to the properties of different contents and storage requirements, aluminum-plastic composite films can be composed of different types of plastic layers and aluminum-plated films.

[0003] The existing method for preparing aluminum film packaging bags is to use a dry composite process to bond the surface layer with aluminum foil, a protective layer and a heat-sealing layer after the surface layer is printed, and then put them in a drying room for curing, and finally cut and make bags. This method has a short production cycle, and the adhesive is generally a polyurethane adhesive. Due to the poor cooking resistance of the polyurethane adhesive, the existing aluminum film packaging bags generally have the phenomenon of composite delamination and leakage after high-temperature cooking, and even bag breakage, causing the food packaged in the bag to deteriorate. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance composite aluminum film packaging bag and a preparation method thereof, so as to solve the problem that the existing composite aluminum film packaging bag has poor cooking resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-performance composite aluminum film packaging bag has a three-layer structure, which includes, from outside to inside, an aluminum-plated film layer, an intermediate film layer and a heat-sealing film layer, wherein the aluminum-plated film layer, the intermediate film layer and the heat-sealing film layer are connected by a two-component polyurethane adhesive.

[0007] Preferably, the two-component polyurethane adhesive comprises a main agent and a curing agent, and the mass ratio of the main agent to the curing agent is 100:18-20.

[0008] Preferably, the main agent preparation process is as follows:

[0009] The polyether polyol was vacuum dehydrated at 120°C for 2h, and after cooling, isophorone diisocyanate and stannous octoate were added, and under nitrogen protection, the reaction was stirred at 80°C for 2-3h, and then diethylene glycol was added, and the reaction was continued at 80°C for 2-4h. Functional fillers were added, stirred for 1h, and the temperature was lowered to 40°C to obtain the main agent.

[0010] Preferably, in the above preparation process, the mass ratio of polyether polyol, isophorone diisocyanate, stannous octoate, diethylene glycol and functional filler is 25-35:5-15:0.01-0.05:3-5:5-10.

[0011] Preferably, the polyether polyol is polyether polyol MN-700.

[0012] Preferably, the curing agent is HDI trimer, and more preferably N3390 produced by Bayer.

[0013] Preferably, the functional filler is a menthol-loaded Ti3AlC2 / SiO2 composite material modified by distearoylphosphatidylethanolamine-polyethylene glycol-silane (DSPE-PEG-Silane).

[0014] Preferably, the preparation process of the functional filler is as follows:

[0015] Distearoylphosphatidylethanolamine-polyethylene glycol-silane and deionized water are mixed, stirred at 45-60°C for 20-30 minutes to obtain a hydrolyzate, the menthol-loaded Ti3AlC2 / SiO2 composite material is placed in a blender, and the hydrolyzate is sprayed on the surface of the menthol-loaded Ti3AlC2 / SiO2 composite material while stirring at 25-32°C. After spraying, the mixture is naturally dried at 25-32°C to obtain a functional filler.

[0016] Preferably, in the above-mentioned preparation process, the mass ratio of the hydrolyzate and the Ti3AlC2 / SiO2 composite material loaded with menthol is 0.5-1.5:5, the amount ratio of distearoylphosphatidylethanolamine-polyethylene glycol-silane and deionized water in the hydrolyzate is 1g:5-10mL, and distearoylphosphatidylethanolamine-polyethylene glycol-silane is added to water, and the -Si(OCH2CH3)3 structure in the distearoylphosphatidylethanolamine-polyethylene glycol-silane molecular chain undergoes a hydrolysis reaction to produce silanol (-Si-OH)3, and the silanol can undergo a condensation reaction with the surface hydroxyl group of the Ti3AlC2 / SiO2 composite material loaded with menthol to complete the modification and obtain a functional filler.

[0017] Preferably, the preparation process of the menthol-loaded Ti3AlC2 / SiO2 composite material is as follows:

[0018] Menthol was added to dimethyl sulfoxide, and the mixture was stirred for 5-10 minutes. Then, the Ti3A l C2 / SiO2 composite material was added thereto, and the mixture was stirred and mixed at 60° C. for 2-4 hours. The mixture was centrifuged, precipitated and dried to obtain the Ti3A l C2 / SiO2 composite material loaded with menthol.

[0019] Preferably, in the above preparation process, the usage ratio of menthol, dimethyl sulfoxide and Ti3A1C2 / SiO2 composite material is 2-5g:20-50mL:1-3g, menthol is dissolved in dimethyl sulfoxide, and menthol is loaded by the pores of Ti3A1C2 / SiO2 composite material to obtain Ti3A1C2 / SiO2 composite material loaded with menthol.

[0020] Preferably, the melting point of menthol is 34-36°C.

[0021] Preferably, the preparation process of Ti3AlC2 / SiO2 composite material is as follows:

[0022] S1, mixing sodium fluoride and hydrochloric acid solution evenly, adding Ti3A l C2 in batches, and then treating at 60°C for 48h to obtain pretreated Ti3A l C2;

[0023] S2. Add the pretreated Ti3A1C2 into deionized water, add hexadecyltrimethylammonium bromide and urea after ultrasonic treatment for 20 minutes, continue ultrasonic treatment for 60 minutes, add n-pentanol cyclohexane mixed solution dropwise, stir for 5 minutes after the addition is complete, add tetraethyl orthosilicate, stir for 40 minutes, transfer to a reactor, react at 120°C for 4 hours, after the reaction is completed, centrifuge, wash the precipitate with anhydrous ethanol and dry to obtain a dry sample; disperse the dry sample in an ethanol solution, add concentrated hydrochloric acid, stir at 60°C for 4 hours, centrifuge, wash the precipitate with anhydrous ethanol and dry to obtain a Ti3A1C2 / SiO2 composite material.

[0024] Ti3AlC2 is a two-dimensional ternary layered material with the advantages of high specific surface area, good electrical conductivity, high elastic modulus and corrosion resistance. The present invention uses it as a substrate, tetraethyl orthosilicate as a silicon source, and hexadecyltrimethylammonium bromide as a template to grow mesoporous silica on the surface of Ti3AlC2 to obtain a Ti3AlC2 / SiO2 composite material.

[0025] Preferably, the usage ratio of sodium fluoride, hydrochloric acid solution and Ti3AlC2 in S1 is 1-2g:20-60mL:2g.

[0026] Preferably, the concentration of the hydrochloric acid solution in S1 is 9-12M.

[0027] Preferably, the dosage ratio of pretreated Ti3AlC2, deionized water, hexadecyltrimethylammonium bromide, urea, n-pentanol cyclohexane mixed solution, tetraethyl orthosilicate, ethanol solution and concentrated hydrochloric acid in S2 is 10 mg: 40 mL: 0.5 g: 0.3 g: 40-41.5 mL: 1.6 mL: 48 mL: 4 mL.

[0028] Preferably, the n-pentanol-cyclohexane mixed solution in S2 is composed of n-pentanol and cyclohexane in a volume ratio of 1-1.5:39-400.

[0029] Preferably, the mass fraction of the ethanol solution in S2 is 50-80%, and the mass fraction of the concentrated hydrochloric acid is 36-38%.

[0030] Preferably, the molecular weight of distearoylphosphatidylethanolamine-polyethylene glycol-silane is 1-5K.

[0031] Preferably, the molecular structure of distearoyl phosphatidylethanolamine-polyethylene glycol-silane is as follows:

[0032] It is obtained by bridging DSPE (1,2-distearoyl-sn-glycero-3-phosphoethanolamine) and silane groups with PEG (polyethylene glycol). It contains 18 highly hydrophobic saturated carbons and phospholipids as well as silane groups. The silane groups on the molecules are highly reactive to materials such as silica.

[0033] Preferably, the aluminized film layer is composed of an aluminized film, which is at least one of polyester aluminized film (VMPET), biaxially oriented polypropylene aluminized film (VMBOPP), cast polypropylene aluminized film (VMCPP) and polyethylene aluminized film (VMPE), and has a thickness of 5-10 μm.

[0034] Preferably, the middle film layer is composed of a biaxially stretched film, and the biaxially stretched film is a biaxially stretched polyurethane film or a biaxially stretched nylon film, and has a thickness of 10-20 μm.

[0035] Preferably, the heat-sealing film layer is composed of a cast polypropylene film with a thickness of 50-150 μm.

[0036] The method for preparing the high-performance composite aluminum film packaging bag comprises the following steps:

[0037] Step 1, mixing the main agent and the curing agent evenly to obtain a two-component polyurethane adhesive, adding ethyl acetate to dilute the two-component polyurethane adhesive to obtain a rubber material for standby use;

[0038] Step 2, coating the rubber on one side of the aluminized film, drying at 78-85°C for 5 minutes, then hot-pressing the biaxially oriented film on the side of the aluminized film coated with the rubber, the temperature of the hot pressing roller is 40-70°C, then aging at 50-55°C for 24-48 hours, and cooling to room temperature to obtain an intermediate film;

[0039] Step 3, coating the rubber material on the side of the intermediate film away from the aluminum-plated film, drying at 78-85°C for 5 minutes, and then hot-pressing the cast polypropylene film on the side of the intermediate film coated with the rubber material, with the temperature of the hot pressing roller at 40-70°C, and then aging at 50-55°C for 24-48 hours, and cooling to room temperature to obtain a composite aluminum film;

[0040] Step 4: Make the composite aluminum film into bags through a three-side sealing bag making machine.

[0041] Preferably, the mass ratio of ethyl acetate to the two-component polyurethane adhesive is 1.3-1.6:1.

[0042] Preferably, the coating amount of the rubber is 4-5 g / m 2 .

[0043] Beneficial effects of the present invention:

[0044] The present invention provides a high-performance composite aluminum film packaging bag, comprising an aluminum-plated film layer, an intermediate film layer and a heat-sealing film layer. By optimizing the composition of the adhesive, not only a close connection between the layers is achieved, but also the adhesion of the adhesive under high temperature and high humidity conditions is greatly improved, thereby ensuring the cooking resistance of the packaging bag. In addition, the packaging bag also has a certain heat storage performance, which can better maintain the stability of the internal temperature and optimize the consumer's use experience. For example, in food packaging, the heat storage material can maintain the temperature of the food, so that consumers can immediately enjoy the food with the best taste after purchase. In addition, the heat storage material can also reduce the deformation and rupture of the packaging bag during refrigeration or freezing, thereby maintaining the integrity and aesthetics of the packaging.

[0045] The two-component polyurethane adhesive of the present invention contains a Ti3AlC2 / SiO2 composite material loaded with distearoylphosphatidylethanolamine-polyethylene glycol-silane modified menthol, which can improve the boiling resistance of the adhesive through the barrier effect of the sheet layer, the hydrophobic effect of the alkyl long chain, the complexation of the phosphate ester and the reinforcing effect of the inorganic filler. The material also contains menthol, which has a melting point of 34-36°C, is in a solid state below 34°C and is in a liquid state above 36°C. The conversion between the liquid and the solid will absorb or release a large amount of heat, which is helpful to maintain the temperature stability inside the package. The high thermal conductivity of the Ti3AlC2 material improves the heat transfer rate of the system, which is conducive to enhancing the temperature control effect. In addition, the menthol has a cool smell and a certain insect repellent effect, which can prevent the packaging bag from being scratched by insects or cockroaches and contaminating food. DETAILED DESCRIPTION

[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0048] Preparation Example 1

[0049] The steps for preparing functional fillers are as follows:

[0050] Mix 1 g of distearoylphosphatidylethanolamine-polyethylene glycol-silane and 5 mL of deionized water, stir at 45 °C for 20 min to obtain a hydrolyzate, put 10 g of menthol-loaded Ti3A l C2 / SiO2 composite material in a blender, and spray 1 g of the hydrolyzate on the surface of the menthol-loaded Ti3A l C2 / SiO2 composite material while stirring at 25 °C. After spraying, dry naturally at 25 °C to obtain a functional filler.

[0051] The preparation process of menthol-loaded Ti3AlC2 / SiO2 composite material is as follows:

[0052] 20 g of menthol was added to 200 mL of dimethyl sulfoxide, and after stirring for 5 min, 10 g of Ti3A l C2 / SiO2 composite material was added, and the mixture was stirred and mixed at 60°C for 2 h. The mixture was centrifuged, and the precipitate was dried to obtain a Ti3A l C2 / SiO2 composite material loaded with menthol.

[0053] The preparation process of Ti3AlC2 / SiO2 composite material is as follows:

[0054] S1. Mix 10 g of sodium fluoride and 200 mL of 9 M hydrochloric acid solution, add 20 g of Ti3AlC2 in equal amounts in 4 times, each time with an interval of 5 min, and then treat at 60°C for 48 h to obtain pretreated Ti3AlC2;

[0055] S2. Add 10g of pretreated Ti3A1C2 into 40L of deionized water, add 500g of hexadecyltrimethylammonium bromide and 300g of urea after ultrasonic treatment for 20min, continue ultrasonic treatment for 60min, add 40L of n-pentanol-cyclohexane mixed solution dropwise, stir for 5min after the addition is complete, add 1.6L of tetraethyl orthosilicate, stir for 40min, transfer to a reactor, react at 120℃ for 4h, after the reaction is completed, centrifuge, wash the precipitate with anhydrous ethanol and dry to obtain a dry sample; disperse the dry sample in 48L of ethanol solution, add 4L of concentrated hydrochloric acid, stir at 60℃ for 4h, centrifuge, wash the precipitate with anhydrous ethanol and dry to obtain a Ti3A1C2 / SiO2 composite material.

[0056] The n-pentanol-cyclohexane mixed solution in S2 is composed of n-pentanol and cyclohexane in a volume ratio of 1:400. The mass fraction of the ethanol solution in S2 is 50%, and the mass fraction of concentrated hydrochloric acid is 36%.

[0057] The molecular weight of distearoylphosphatidylethanolamine-polyethylene glycol-silane is 1K.

[0058] Preparation Example 2

[0059] The steps for preparing functional fillers are as follows:

[0060] Mix 1 g of distearoylphosphatidylethanolamine-polyethylene glycol-silane and 10 mL of deionized water, stir at 60°C for 30 min to obtain a hydrolyzate, place 10 g of menthol-loaded Ti3A l C2 / SiO2 composite material in a blender, and spray 3 g of the hydrolyzate on the surface of the menthol-loaded Ti3A l C2 / SiO2 composite material while stirring at 32°C. After spraying, dry naturally at 32°C to obtain a functional filler.

[0061] The preparation process of the menthol-loaded Ti3AlC2 / SiO2 composite material is as follows:

[0062] 50 g of menthol was added to 500 mL of dimethyl sulfoxide, and after stirring for 10 min, 30 g of Ti3A1C2 / SiO2 composite material was added, and the mixture was stirred and mixed at 60°C for 4 h. The mixture was centrifuged, and the precipitate was dried to obtain a Ti3A1C2 / SiO2 composite material loaded with menthol.

[0063] The preparation process of Ti3AlC2 / SiO2 composite material is the same as that of Preparation Example 1.

[0064] The molecular weight of distearoylphosphatidylethanolamine-polyethylene glycol-silane is 5K.

[0065] Comparative Example 1

[0066] The preparation of the functional filler is different from that in Preparation Example 1, except that an equal mass of the Ti3A l C2 / Si O2 composite material is used to replace an equal mass of the menthol-loaded Ti3A l C2 / Si O2 composite material, and the preparation process of the Ti3A l C2 / Si O2 composite material is the same as that in Preparation Example 1.

[0067] Comparative Example 2

[0068] The preparation of the functional filler is different from that in Preparation Example 1, except that the same mass of the menthol-loaded SiO2 composite material is used to replace the same mass of the menthol-loaded Ti3AlC2 / SiO2 composite material. The preparation process of the menthol-loaded SiO2 composite material is as follows:

[0069] 20 g of menthol was added to 200 mL of dimethyl sulfoxide, and after stirring for 5 min, 10 g of mesoporous SiO2 was added, and the mixture was stirred and mixed at 60°C for 2 h. The mixture was centrifuged, precipitated and dried to obtain a menthol-loaded SiO2 composite material, wherein the mesoporous SiO2 was SBA-15.

[0070] Comparative Example 3

[0071] This control example is a menthol-loaded Ti3AlC2 / SiO2 composite material. The preparation process of the menthol-loaded Ti3AlC2 / SiO2 composite material is the same as that of Preparation Example 1.

[0072] Example 1

[0073] A method for preparing a high-performance composite aluminum film packaging bag comprises the following steps:

[0074] Step 1, the main agent and the curing agent are mixed uniformly according to the mass ratio of 100:18 to obtain a two-component polyurethane adhesive, and ethyl acetate is added in an amount of 1.3 times the mass of the two-component polyurethane adhesive to dilute the mixture to obtain a sizing material for standby use;

[0075] Step 2: Apply the adhesive to one side of the aluminum film. The amount of adhesive applied is 4g / m 2 , dried at 78°C for 5 minutes, then hot-pressed the biaxially stretched film onto the side of the aluminized film coated with the rubber material, the hot-pressing roller temperature was 40°C, then aged at 50°C for 24 hours, and cooled to room temperature to obtain an intermediate film;

[0076] Step 3: Apply the rubber to the side of the intermediate film away from the aluminized film. The amount of rubber applied is 4g / m 2 , dried at 78°C for 5 minutes, then hot-pressed the cast polypropylene film on the side of the intermediate film coated with the rubber material, the hot pressing roller temperature was 40°C, and then aged at 50°C for 24 hours, and cooled to room temperature to obtain a composite aluminum film;

[0077] Step 4: Make the composite aluminum film into bags through a three-side sealing bag making machine.

[0078] The aluminized film is a polyester aluminized film (VMPET) with a thickness of 10 μm.

[0079] The biaxially oriented film is a biaxially oriented polyurethane film with a thickness of 15 μm.

[0080] The cast polypropylene film had a thickness of 100 μm.

[0081] The main agent preparation process is as follows:

[0082] 25 parts by weight of polyether polyol were vacuum dehydrated at 120°C for 2 hours, and after cooling, 5 parts by weight of isophorone diisocyanate and 0.01 parts by weight of stannous octoate were added, and the mixture was stirred and reacted at 80°C for 2 hours under nitrogen protection. Then, 3 parts by weight of diethylene glycol were added, and the reaction was continued at 80°C for 2 hours. 5 parts by weight of the functional filler of Preparation Example 1 were added, stirred for 1 hour, and the mixture was cooled to 40°C to obtain the main agent.

[0083] The polyether polyol is polyether polyol MN-700.

[0084] The curing agent is HD I trimer, which is N3390 produced by Bayer.

[0085] Example 2

[0086] A method for preparing a high-performance composite aluminum film packaging bag comprises the following steps:

[0087] Step 1, the main agent and the curing agent are mixed uniformly according to a mass ratio of 100:19 to obtain a two-component polyurethane adhesive, and ethyl acetate is added in an amount of 1.5 times the mass of the two-component polyurethane adhesive to dilute the mixture to obtain a sizing material for standby use;

[0088] Step 2: Apply the adhesive to one side of the aluminum film. The amount of adhesive applied is 4.5g / m 2 , dried at 80°C for 5 minutes, then hot-pressed the biaxially stretched film onto the side of the aluminized film coated with the rubber material, the hot-pressing roller temperature was 60°C, then aged at 52°C for 40 hours, and cooled to room temperature to obtain an intermediate film;

[0089] Step 3: Apply the rubber to the side of the intermediate film away from the aluminized film. The amount of rubber applied is 4.5g / m 2 , dried at 80°C for 5 minutes, then hot-pressed the cast polypropylene film on the side of the intermediate film coated with the rubber material, the temperature of the hot pressing roller was 60°C, and then aged at 52°C for 40 hours, and cooled to room temperature to obtain a composite aluminum film;

[0090] Step 4: Make the composite aluminum film into bags through a three-side sealing bag making machine.

[0091] The aluminized film, biaxially stretched film and cast polypropylene film are the same as those in Example 1.

[0092] The main agent preparation process is as follows:

[0093] 30 parts by weight of polyether polyol were vacuum dehydrated at 120°C for 2 hours, and after cooling, 10 parts by weight of isophorone diisocyanate and 0.03 parts by weight of stannous octoate were added, and the mixture was stirred at 80°C for 2.5 hours under nitrogen protection. Then, 4 parts by weight of diethylene glycol were added, and the reaction was continued at 80°C for 3 hours. 8 parts by weight of the functional filler of Preparation Example 1 were added, stirred for 1 hour, and the mixture was cooled to 40°C to obtain the main agent.

[0094] The polyether polyol is polyether polyol MN-700.

[0095] The curing agent is HD I trimer, which is N3390 produced by Bayer.

[0096] Example 3

[0097] A method for preparing a high-performance composite aluminum film packaging bag comprises the following steps:

[0098] Step 1, the main agent and the curing agent are mixed uniformly according to a mass ratio of 100:20 to obtain a two-component polyurethane adhesive, and ethyl acetate is added in an amount of 1.6 times the mass of the two-component polyurethane adhesive to dilute the mixture to obtain a sizing material for standby use;

[0099] Step 2: Apply the adhesive to one side of the aluminum film. The amount of adhesive applied is 5g / m 2 , dried at 85°C for 5 minutes, then hot-pressed the biaxially stretched film onto the side of the aluminized film coated with the rubber material, the hot-pressing roller temperature was 70°C, then aged at 55°C for 48 hours, and cooled to room temperature to obtain an intermediate film;

[0100] Step 3: Apply the rubber to the side of the intermediate film away from the aluminized film. The amount of rubber applied is 5g / m 2 , dried at 85°C for 5 minutes, then hot-pressed the cast polypropylene film on the side of the intermediate film coated with the rubber material, the hot pressing roller temperature was 70°C, and then aged at 55°C for 48 hours, and cooled to room temperature to obtain a composite aluminum film;

[0101] Step 4: Make the composite aluminum film into bags through a three-side sealing bag making machine.

[0102] The aluminized film, biaxially stretched film and cast polypropylene film are the same as those in Example 1.

[0103] The main agent preparation process is as follows:

[0104] 35 parts by weight of polyether polyol were vacuum dehydrated at 120°C for 2 hours, and after cooling, 15 parts by weight of isophorone diisocyanate and 0.05 parts by weight of stannous octoate were added, and the mixture was stirred and reacted at 80°C for 3 hours under nitrogen protection. Then, 5 parts by weight of diethylene glycol were added, and the reaction was continued at 80°C for 4 hours. 10 parts by weight of the functional filler of Preparation Example 2 were added, stirred for 1 hour, and the mixture was cooled to 40°C to obtain the main agent.

[0105] The polyether polyol is polyether polyol MN-700.

[0106] The curing agent is HD I trimer, which is N3390 produced by Bayer.

[0107] Example 4

[0108] A method for preparing a high-performance composite aluminum film packaging bag, compared with Example 1, the only difference is that the weight of the functional filler in the preparation process of the main agent is adjusted from "5 parts by weight" to "10 parts by weight".

[0109] Example 5

[0110] A method for preparing a high-performance composite aluminum film packaging bag, compared with Example 3, the only difference is that the weight of the functional filler in the main agent during the preparation process is adjusted from "10 parts by weight" to "5 parts by weight".

[0111] Example 6

[0112] A method for preparing a high-performance composite aluminum film packaging bag, compared with Example 1, the only difference is that the aluminized film is a polyester aluminized film (VMPET) with a thickness of 7 μm, the biaxially stretched film is a biaxially stretched polyurethane film with a thickness of 10 μm, and the cast polypropylene film has a thickness of 50 μm.

[0113] Example 7

[0114] A method for preparing a high-performance composite aluminum film packaging bag, compared with Example 1, the only difference is that the aluminized film is a polyester aluminized film (VMPET) with a thickness of 5 μm, the biaxially stretched film is a biaxially stretched polyurethane film with a thickness of 20 μm, and the cast polypropylene film has a thickness of 150 μm.

[0115] Example 8

[0116] A method for preparing a high-performance composite aluminum film packaging bag, compared with Example 1, the only difference is that the aluminized film is a biaxially oriented polypropylene aluminized film (VMBOPP).

[0117] Comparative Example 1

[0118] A method for preparing a high-performance composite aluminum film packaging bag, compared with Example 1, the only difference is that the "functional filler" in Example 1 is replaced by the product prepared in Control Example 1.

[0119] Comparative Example 2

[0120] A method for preparing a high-performance composite aluminum film packaging bag, compared with Example 1, the only difference is that the "functional filler" in Example 1 is replaced by the product prepared in Control Example 2.

[0121] Comparative Example 3

[0122] A method for preparing a high-performance composite aluminum film packaging bag, compared with Example 1, the only difference is that the "functional filler" in Example 1 is replaced by the substance in Control Example 3.

[0123] The composite aluminum films and packaging bags obtained in Examples 1 to 8 and Comparative Examples 1 to 3 were subjected to performance tests, and the test process was as follows:

[0124] Peel strength: The pattern was made into a 15mm wide and 200mm long strip, and the peel strength between the aluminum-plated film layer and the middle film layer in each group of composite aluminum films was tested at a speed of 250mm / min using a GGBL-L electronic tensile testing machine. The same sample was tested 5 times, and the average peel force was recorded;

[0125] Peel strength after high-temperature cooking: Place each group of composite aluminum films in a ZM-100 reverse pressure cooking sterilizer and cook at 135°C for 30 minutes at a pressure of 0.2MPa. Then take them out and cool them down, and then test the peel strength again according to the above method;

[0126] Temperature regulation performance: ice cubes were packed in each group of packaging bags and refrigerated at -10℃ for 2 hours, then taken out and placed at room temperature of 38℃ for 10 minutes, and the volume of melted water was collected;

[0127] Insect repellent effect: tested according to the insect repellent effect test method disclosed in the Chinese patent application number 2021114054399;

[0128] The results are shown in Table 1:

[0129] Table 1

[0130]

[0131] Analyzing the data recorded in Table 1, it can be seen that the peel strength between the aluminum-plated film layer and the intermediate film layer in the packaging bags in Examples 1 to 8 is lower in Example 5, and higher in the others, which is mainly due to the lower content of the functional filler, and Example 4 has the best comprehensive performance, indicating that the packaging bag prepared by the present invention has good boiling resistance, temperature regulation and insect repellent effects. Specifically, it can be seen from the test results in Example 1 and Comparative Example 1 that the absence of menthol will cause the temperature regulation performance and insect repellent effect of the packaging bag to be significantly reduced. It can be seen from the test results in Example 1 and Comparative Example 2 that the absence of Ti3A1C2 will cause the temperature regulation performance and boiling resistance of the packaging bag to be significantly reduced. It can be seen from the test results in Example 1 and Comparative Example 3 that the absence of distearoylphosphatidylethanolamine-polyethylene glycol-silane will cause the peel strength and boiling resistance of the packaging bag to be significantly reduced.

[0132] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0133] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-performance composite aluminum film packaging bag, having a three-layer structure, which includes, from the outside to the inside, an aluminum-plated film layer, an intermediate film layer and a heat-sealing film layer, wherein the aluminum-plated film layer, the intermediate film layer and the heat-sealing film layer are connected by a two-component polyurethane adhesive, characterized in that: Two-component polyurethane adhesive includes a main agent and a curing agent. The preparation process of the main agent is as follows: The polyether polyol was vacuum dehydrated at 120°C for 2h, and after cooling, isophorone diisocyanate and stannous octoate were added, and the mixture was stirred at 80°C for 2-3h under nitrogen protection, and then diethylene glycol was added, and the mixture was continued to react at 80°C for 2-4h, and functional fillers were added, stirred for 1h, and the mixture was cooled to 40°C to obtain the main agent; The functional filler is a Ti3AlC2 / SiO2 composite material loaded with menthol modified by distearoylphosphatidylethanolamine-polyethylene glycol-silane.

2. A high-performance composite aluminum film packaging bag according to claim 1, characterized in that: The mass ratio of polyether polyol, isophorone diisocyanate, stannous octoate, diethylene glycol and functional filler is 25-35:5-15:0.01-0.05:3-5:5-10.

3. A high-performance composite aluminum film packaging bag according to any one of claims 1-2, characterized in that: The preparation process of functional fillers is as follows: Distearoylphosphatidylethanolamine-polyethylene glycol-silane and deionized water are mixed, stirred at 45-60°C for 20-30 minutes to obtain a hydrolyzate, the menthol-loaded Ti3AlC2 / SiO2 composite material is placed in a blender, and the hydrolyzate is sprayed on the surface of the menthol-loaded Ti3AlC2 / SiO2 composite material while stirring at 25-32°C. After spraying, the mixture is naturally dried at 25-32°C to obtain a functional filler.

4. The high-performance composite aluminum film packaging bag according to claim 3, characterized in that: The mass ratio of the hydrolyzate to the menthol-loaded Ti3AlC2 / SiO2 composite material is 0.5-1.5:5, and the dosage ratio of distearoyl phosphatidylethanolamine-polyethylene glycol-silane to deionized water in the hydrolyzate is 1g:5-10mL.

5. The high-performance composite aluminum film packaging bag according to claim 3, characterized in that: The preparation process of menthol-loaded Ti3AlC2 / SiO2 composite material is as follows: Menthol was added to dimethyl sulfoxide, and the mixture was stirred for 5-10 minutes, and then the Ti3AlC2 / SiO2 composite material was added thereto. The mixture was stirred and mixed at 60°C for 2-4 hours, and the mixture was centrifuged, precipitated and dried to obtain the Ti3AlC2 / SiO2 composite material loaded with menthol.

6. A high-performance composite aluminum film packaging bag according to claim 5, characterized in that: The dosage ratio of menthol, dimethyl sulfoxide and Ti3AlC2 / SiO2 composite material is 2-5g:20-50mL:1-3g.

7. The high-performance composite aluminum film packaging bag according to claim 5, characterized in that: The preparation process of Ti3AlC2 / SiO2 composite material is as follows: S1, mixing sodium fluoride and hydrochloric acid solution evenly, adding Ti3AlC2 in batches, and then treating at 60°C for 48h to obtain pretreated Ti3AlC2; S2. Add the pretreated Ti3AlC2 into deionized water, add hexadecyltrimethylammonium bromide and urea after ultrasonic treatment for 20 minutes, continue ultrasonic treatment for 60 minutes, add n-pentanol cyclohexane mixed solution dropwise, stir for 5 minutes after the addition is complete, add tetraethyl orthosilicate, stir for 40 minutes, transfer to a reactor, react at 120°C for 4 hours, centrifuge after the reaction, wash the precipitate with anhydrous ethanol and dry to obtain a dry sample; disperse the dry sample in an ethanol solution, add concentrated hydrochloric acid, stir at 60°C for 4 hours, centrifuge, wash the precipitate with anhydrous ethanol and dry to obtain a Ti3AlC2 / SiO2 composite material.

8. The high-performance composite aluminum film packaging bag according to claim 7, characterized in that: The dosage ratio of sodium fluoride, hydrochloric acid solution and Ti3AlC2 in S1 is 1-2g:20-60mL:2g, and the concentration of hydrochloric acid solution is 9-12M.

9. The high-performance composite aluminum film packaging bag according to claim 7, characterized in that: The dosage ratio of pretreated Ti3AlC2, deionized water, hexadecyltrimethylammonium bromide, urea, n-pentanol-cyclohexane mixed solution, tetraethyl orthosilicate, ethanol solution and concentrated hydrochloric acid in S2 is 10 mg: 40 mL: 0.5 g: 0.3 g: 40-41.5 mL: 1.6 mL: 48 mL: 4 mL. The n-pentanol-cyclohexane mixed solution is composed of n-pentanol and cyclohexane in a volume ratio of 1-1.5: 39-400, and the mass fraction of the ethanol solution is 50-80%.

10. A method for preparing a high-performance composite aluminum film packaging bag according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, mixing the main agent and the curing agent evenly to obtain a two-component polyurethane adhesive, and adding ethyl acetate to dilute the two-component polyurethane adhesive to obtain a rubber material; Step 2, coating the rubber on one side of the aluminized film, drying at 78-85°C for 5 minutes, then hot-pressing the biaxially oriented film on the side of the aluminized film coated with the rubber, the temperature of the hot pressing roller is 40-70°C, then aging at 50-55°C for 24-48 hours, and cooling to room temperature to obtain an intermediate film; Step 3, coating the rubber material on the side of the intermediate film away from the aluminum-plated film, drying at 78-85°C for 5 minutes, and then hot-pressing the cast polypropylene film on the side of the intermediate film coated with the rubber material, with the temperature of the hot pressing roller at 40-70°C, and then aging at 50-55°C for 24-48 hours, and cooling to room temperature to obtain a composite aluminum film; Step 4: Bag the composite aluminum film through a three-side sealing bag making machine to obtain a high-performance composite aluminum film packaging bag.

Citation Information

Patent Citations

  • Cooling-resistant plastic aluminum foil compound bag and preparation method thereof

    CN102837880A

  • Moisture barrier coating as well as preparation method and application thereof

    CN116102926A

  • Three-dimensional semiconductor devices

    KR1020210008983A

  • Porous nanosheets for effective adsorption of small molecules and volatile organic compounds

    US20220219993A1